Piper cubeba L. f. Nanoemulsion: Formulation and Effect on Antioxidant Activity in Rat's Hippocampus and Prefrontal Cortex - Dwita, Lusi Putri; Iwo, Maria Immaculata; Mauludin, Rachmat; Elfahmi, Elfahmi (Borneo Journal of Pharmacy, 2025)
The previous study showed that Piper cubeba extract increased brain antioxidant capacity, alleviating cognitive impairment in rats. However, brain-targeted drug delivery is often limited by the blood-brain barrier. One of the approaches to overcome this obstacle is nanocarrier. This study aimed to formulate a nanoemulsion (NE) of P. cubeba extract and determine the antioxidant activity in the brain. The research begins with the determination of excipients and the formula of NE. The formula was then tested for globule size, polydispersity index, thermodynamic stability, zeta potential, pH, and viscosity. The globule's shape was determined using transmission electron microscopy (TEM). The antioxidant activity was tested by catalase and lipid peroxidase activity in the brain after giving NE orally for seven days. Formulations of NE resulted in nano-size globules and were stable thermodynamically. The NE formula significantly increased catalase and inhibited lipid peroxidase activities in the Rat's hippocampus and prefrontal cortex. This study resulted in a stable formula and low-cost production of P. cubeba extract NE, which is active as the brain's antioxidant and is feasible to develop as a neuroprotective agent for various neurodegenerative diseases.